THE EFFECT OF BANK INTERNAL VARIABLES AND MACROECONOMIC VARIABLES ON FINANCIAL PERFORMANCE (STUDY OF SHARIA COMMERCIAL BANKS IN INDONESIA DURING THE 2014-2018 PERIOD) - Annisa Rahma Febriyanti; Atina Shofawati (Universitas Airlangga, 2020)
This research aims to find out the effect of bank internal variabel and macroeconomics variabel toward islamic banks financial performance proxied by Return on Assets (ROA) simultaneously and partially. Bank internal variables consist of capital structure, operational efficiency, asset quality, and liquidity, while macroeconomics variables consist of inflation and real GDP growth. Methodology that used in this study is quantitative approach using panel regression as technique analysis. Sampel used 11 Islamic Bank in Indonesia regulated by Otoritas Jasa Keuangan and launched legally before 2014. Data collected from annual report 2014 until 2018 from each banks. Result found that capital structure, operational efficiency, dan asset quality have significantly negative effects on Return on Assets (ROA). Liquidity has positive significantly effects on Return on Assets. Inflation and Real GDP Growth have insignificantly affects Islamic Commercial Bank’s Financial Performance measured by Return on Assets.Keywords: Return on Assets, Capital Structure, Operational Efficiency, Assets Quality, Liquidity, Macroeconomic, Islamic Commercial Bank